Utilization of extracted protein from fish fin and chicken feather waste for alkaline protease production by indigenous bacteria - Thanoon, Raid D.; Subramaniam, Rubaaini; Makky, Essam A.; M. M., Yusoff (JJBS, 2018)

(untitled)
Environmental pollution is a major problem in the developed and developing countries. Fish fins (FF) and chicken feathers (CF) can be sources of solid waste contamination; hence, both FF and CF were investigated for alkaline protease (AP) production through microbial degradation. Proteins were extracted from these samples and added into the production medium containing the bacterial suspension, and assayed for AP production. The process parameters were optimized by OFAT and the optimum conditions for CF and FF were pH 9.0, temperature of 28°C for CF and 40°C for FF, incubation period was 6 and 10 days for CF and FF, respectively. The optimum carbon source was galactose and glucose for CF and FF respectively, and the optimum nitrogen source was ammonium chloride and beef extract, respectively. The inoculum size of 1.5 mL and a protein volume of 0.5 and 2.0 mL for CF and FF, respectively was recorded. The present study indicates the protein was successfully extracted from the waste used and degraded by AP enzyme that produced and optimized using OFAT by indigenous bacterial isolates.